Metagenomics analysis of the neonatal intestinal resistome - Leo, Stefano; Cetiner, Omer F.; Pittet, Laure F.; Messina, Nicole L.; Jakob, William; Falquet, Laurent; Curtis, Nigel; Zimmermann, Petra (Frontiers in Pediatrics, 2023)
Introduction: The intestinal microbiome forms a major reservoir for antibiotic resistance genes (ARGs). Little is known about the neonatal intestinal resistome. Objective: To investigate the intestinal resistome and factors that influence the abundance of ARGs in a large cohort of neonates. Methods: Shotgun metagenomics was used to analyse the resistome in stool samples collected at one week of age from 390 healthy, term-born neonates who did not receive antibiotics. Results: Overall, 913 ARGs belonging to 27 classes were identified. The most abundant ARGs were those conferring resistance to tetracyclines, quaternary ammonium compounds, and macrolide-lincosamide-streptogramin-B. Phylogenetic composition was strongly associated with the resistome composition. Other factors that were associated with the abundance of ARGs were delivery mode, gestational age, birth weight, feeding method and antibiotics in the last trimester of pregnancy. Sex, ethnicity, probiotic use during pregnancy, and intrapartum antibiotics had little effect on the abundance of ARGs. Conclusion: Even in the absence of direct antibiotic exposure, the neonatal intestine harbours a high abundance and variety of ARGs.